ChemInform Abstract: Fe2 (SO4) 3·H2SO4·28H2O, a Low‐Temperature Water‐Rich Iron(III) Sulfate. Issue 29 (1st July 2013) - Schmidt, Horst; Hennings, Erik; Zuerner, Philipp; Voigt, Wolfgang
Abstract Violet crystals of the title compound are obtained from aqueous solutions of Fe2(SO4)3 containing 5—20% H2SO4 (235—239 K).